Patterns of Substance Abuse Among Young Males in Hargeisa of Somaliland: A Mixed-Method Exploration - Omer Aden, Mohamed; BakiBillah, Abul Hasan; Khandkar, Salamat (Health Nexus, 2024)
This mixed method study was designed to explore substance abuse in Hargeisa. Total 300 participants were interviewed for quantitative data and 50 respondents were in-depth interviewed for qualitative data. The findings indicate that Khat is the most commonly used substance at a rate of 45%. Moreover, 48% of respondents reported using other drugs such as tobacco, prescription medications (e.g., opioids, benzodiazepines), stimulants like Adderall or Ritalin, and cocaine. Furthermore, participants aged between 19-21 years old constituted 41% of the sample. This age group present a distinct characteristic indicating variations in substance preferences. Respondents of non-formal education group (43%) showed higher contribution to substance abuse compared to those with high school education (39%), whereas university level individuals accounted for only 18%. This study also found a higher percent of substance abuse among unemployed group suggesting a potential correlation between joblessness and substance misuse. In-depth interview reveals that participants' perspectives were shaped by various cultural influences, including views on masculinity and societal norms. Recognizing this diversity is crucial for tailored interventions. Additionally, participants emphasized both the advantages and disadvantages of substance use. Some regarded substances as a way to reduce stress, boredom, or social anxiety during difficult times such as economic crisis, political instability and wide range of unemployment. However, they also acknowledged significant drawbacks such as adverse health effects, financial troubles, and strained relationships.